Reliability-aware zonotopic tube-based model predictive control of a drinking water network - Khoury, Boutrous; Nejjari, Fatiha; Puig, Vicenç (Zielona Góra: Uniwersytet Zielonogórski)
A robust economic model predictive control approach that takes into account the reliability of actuators in a network is presented for the control of a drinking water network in the presence of uncertainties in the forecasted demands required for the predictive control design. The uncertain forecasted demand on the nominal MPC may make the optimization process intractable or, to a lesser extent, degrade the controller performance. Thus, the uncertainty on demand is taken into account and considered unknown but bounded in a zonotopic set.
Keywords: fault-tolerant control; reliability; robust MPC; zonotopes; Bayesian theory; drinking water network